Work, ontology, and method: foundations of the ethical-political project of Social Work (Temporalis, 2026)
This study examines the importance of the historical-dialectical materialist method and of labor in the formation of the social being, based on the contributions of Karl Marx and György Lukács. It emphasizes the relevance of this method for understanding historical changes and for the ethical-political project of Social Work in Brazil. The objective is to demonstrate that the ontology of the social being, grounded in the category of labor, provides the theoretical and methodological foundation that supports a critical and emancipatory professional practice. The research adopts a qualitative approach of a theoretical and bibliographical nature, organized around three central axes: the ontology of the social being according to Lukács, the definition of labor as teleological positing, and the historical-dialectical materialist method as the foundation of Social Work. The results suggest that the method, by considering totality and contradiction as the foundations of reality, enables the understanding of the manifestations of the social question in their complexity and guides professional practice toward human emancipation.
Keywords: Historical-dialectical materialist method; Ontology of social being; Social Work; Labor